2000
DOI: 10.1051/rnd:2000126
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal phosphorus availability from several feedstuffs measured by the nylon bag technique

Abstract: -The present study was aimed at determining rumen phosphorus availability of some feedstuffs assessed with the nylon bag technique: forage (alfalfa), cereals (control-C wheat, formaldehyde treated-FT wheat, barley, corn), cereal by-products (wheat bran, wheat distillers, corn distillers) and meals (C and FT soya bean meals, rapeseed meals and sunflower meals). Rumen phosphorus availability was not uniform amongst the feedstuffs, varying from 33.1% (FT rapeseed meal) to 84.7% (C wheat). Alfalfa phosphorus relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
3
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
6
25
3
1
Order By: Relevance
“…The in situ ruminal degradation of P was inconsistent to the previous study on wheat (a = 61.4%, b =38.9%) (Bravo et al, 2000). The variation might be related to the differences in washing in the in situ procedure, animal diet and differences in sample preparation (Vanzant et al, 1998;Schwab et al, 2003).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…The in situ ruminal degradation of P was inconsistent to the previous study on wheat (a = 61.4%, b =38.9%) (Bravo et al, 2000). The variation might be related to the differences in washing in the in situ procedure, animal diet and differences in sample preparation (Vanzant et al, 1998;Schwab et al, 2003).…”
Section: Resultscontrasting
confidence: 61%
“…It is accepted that phytate P is poorly absorbed by monogastric animals, but could be efficiently utilized by ruminants, due to the high phytase activity of ruminal microorganisms (Konishi et al, 1999). Furthermore, P content and rumen solubilization vary greatly depending on the feedstuffs (Bravo et al, 2000). In addition, concerning the current challenge of reducing P pollution in animal husbandry, it is urgent to decrease dietary P rations of ruminants by reducing the safety margin of excess P (Jonker and Kohn, 1999;Valk and Sebek, 1999;Wu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The variations observed in phytate phosphorus release in the rumen among feedstuffs [1,18] probably indicate that different phytic acid salts are not hydrolysed with the pH, N-NH 3 and total SCFA could indicate that the microbial fermentation activity was not affected by our experimental conditions. The P supply in an inorganic as well as in an organic form, was adequate to meet bacterial requirements [2,6].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to monogastric animals, the InsP 6 is completely available for ruminants, due to a high phytase activity of ruminal microbes (Clark et al, 1986;Morse et al, 1992;Feng et al, 2013). However, other studies have shown that the rumen degradation of InsP 6 may be incomplete (Park et al, 2000;Jarrett et al, 2014), whereby various factors such as feed physical properties, short ruminal retention time Jarrett et al, 2014), and processing of feedstuffs with formaldehyde or heat (Konishi et al, 1999;Park et al, 2000;Bravo et al, 2000) seem to play a role. Newer research data indicate that ruminal degradability of InsP 6 is increased by supplementing exogenous phytase to dairy cow diets, resulting in a higher P availability for ruminal microbiota and the host Brask-Pedersen et al, 2013;Jarrett et al, 2014).…”
Section: Introductionmentioning
confidence: 99%